2018
DOI: 10.19082/7243
|View full text |Cite
|
Sign up to set email alerts
|

The effects of mobile text messages on raising knowledge of men with type 2 diabetes, Isfahan, 2015: an educational experimental study

Abstract: BackgroundDiabetes is one of the most common metabolic disorders which are rapidly increasing. Distance training is a cost-effective, easy and accessible way in which time and place dimensions of communication are removed.ObjectiveTo determine the effects of mobile text messages on raising knowledge of men with type 2 diabetes.MethodsThis educational experiment recruited 76 people selected by convenient sampling from a population of male patients with type 2 diabetes presenting to Sedigheh Tahereh Research Cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
1
0
Order By: Relevance
“…In fact, raising knowledge level is the first steps in changing behavior process. In the present study, the level of knowledge of T2D patients in the experimental group improved significantly after the theory-based educational intervention, which was in line with the findings of previous studies [25][26][27]. It seems that providing simple and understandable information related to the mechanism and cause-and--effect relationships between regular physical activity and the consequences of T2D along with the repetition of educational SMS has led to an increase in the awareness of patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In fact, raising knowledge level is the first steps in changing behavior process. In the present study, the level of knowledge of T2D patients in the experimental group improved significantly after the theory-based educational intervention, which was in line with the findings of previous studies [25][26][27]. It seems that providing simple and understandable information related to the mechanism and cause-and--effect relationships between regular physical activity and the consequences of T2D along with the repetition of educational SMS has led to an increase in the awareness of patients.…”
Section: Discussionsupporting
confidence: 91%
“…It seems that providing simple and understandable information related to the mechanism and cause-and--effect relationships between regular physical activity and the consequences of T2D along with the repetition of educational SMS has led to an increase in the awareness of patients. In line with previous researches, the results of the present study showed the improvement of FBG and HbA1c levels in the experimental group after the theory-based educational intervention [25][26][27][28]. Abaza and Marschollek (2012) emphasized that SMS based education to promote self-management caused a 1% decrease in HbA1c in middle and low-income patients [27].…”
Section: Discussionsupporting
confidence: 91%
“…Education and treatment follow-up have also been investigated in the case of other diseases, and the results are generally in good agreement with the present study. In this regard, Goodarzi et al (40) supported the impact of SMS-based training on the knowledge and awareness of male patients with type 2 diabetes. Hovadick et al (41) found that SMS-based follow-up could boost self-care in pa- In the present study, the telephone follow-up, although not as effective as SMS-based follow-up, outperformed educational booklets in increasing the self-care ability of patients.…”
Section: Discussionmentioning
confidence: 97%